Jewelry box: inspired by (Istana Kenangan) / Nur Afiqah Mohd Azrin - Mohd Azrin, Nur Afiqah (2022)
Istana Kenangan or the Royal museum of Kuala Kangsar. This building is a temporary place for D.Y.M.M The late Sultan Iskandar Shah ordered the museum to built as a temporary residence. This museum’s architecture is an excellent example of cultural architecture. This building was built in 1926 and become to royal museum on November 16, 1986.